Metaphor in James Cameron’s Titanic - Ria Valentine Angela Manalu; Riscitta Ogilvie Hubertus Sinaga; Nayla Azahra; Syamsul Bahri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The Titanic drama contains many figurative expressions that reflect deep emotions, life values, and internal conflicts. These figures of speech are used to describe love, fear, sadness, and hope in a more vivid and memorable way. The emotional experiences of the characters, especially Jack and Rose, are shown not only through direct dialogues but also through creative figurative language. This study aims to examine the types of figures of speech found in Titanic, a drama film directed by James Cameron. Using a qualitative descriptive method, this study analyzes the film's dialogues based on the conceptual figurative theory proposed by Lakoff and Johnson. This study identified three main types of figures of speech: structural, ontological (including personification and metonymy), and orientational figures of speech. The results showed that structural figures of speech were the most dominant type, appearing in 45.9% of the total data, followed by ontological figures of speech at 29.7%, and orientational figures of speech at 24.3%. This finding proves that figures of speech are not only used to beautify language but also to express feelings and views on life in a deeper and more emotional way. The allusions in Titanic help the audience understand the characters' thoughts and experiences better.